Optimizing the Merdeka Curriculum for Developing the Pancasila Student Profile through Project-Based Learning - Nur Hakim, Muhammad; Zakiyatus Solihah, Kiki; Ismail, Feiby; Salim, Arhanuddin; Prasetiyo, Nova Tri (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This study aims to understand the planning and implementation of the Merdeka curriculum in shaping the Pancasila student profile. Employing a qualitative research design with descriptive analysis, the subjects included curriculum vice principals, project teachers, and students. Data were collected through observation, interviews, and documentation, while data validity was ensured through technique and source triangulation. The findings reveal that the implementation of the Merdeka curriculum is at a developing stage, 1) Curriculum planning carried out at the start of the academic year 2022/2023 following a prepared workflow. The school extensively improvises government-provided guidelines in developing the operational curriculum and project modules to better meet student and industry needs. 2) The instructional approach at SMK PK Krian 2 is project-based, with the implementation of (Projek Penguatan Profil Pelajar Pancasila dan Budaya Kerja: P5BK) using monthly blocks to replace intracurricular learning hours after (Masa Pengenalan Lingkungan Sekolah: MPLS) activities, covering five themes to achieve the six dimensions of the Pancasila student profile. Assessment results show that students are progressing towards the goals set in the project modules, yet the full formation of the Pancasila student profile is not yet achieved due to the novelty of the projects. However, educators are optimistic that the Merdeka curriculum will foster changes in student attitudes and is most suitable for the school's conditions.